Wine Makes Good Blood: Wine Culture Among Toronto Italians - Del Giudice, Luisa (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2000)
While the author’s past research on Toronto Italians has explored foods place in the domestic and mythic landscapes of immigrants (from the kitchen, garden, and winecellar of home, to the mythic Land of Cockaigne (Paese di Cuccagnd), “a gastronomic utopia,” still embedded in immigrant consciousness, this paper elaborates the wine nexus and explores the meanings of wine— material and symbolic, historic and contemporary — in the culture of predominately first-generation Toronto Italians. It delineates how wine figures in several primary binary oppositions in Italian folk culture, which oppose 1 ) wine to water; 2) wine to bread; 3) blood to body; and 4) the semantics of red vis à vis white. Further, it focusses on how Italian historic and symbolic contexts intersect with this culture through family history, through personal experience and anecdote, and to a lesser extent through direct historic sources. It provides snapshots of how cultural history and personal experience constantly intertwine within the praxis of folk culture.